A Comprehensive Review of Risk Factors for Sexual Violence, Bullying, and Drug Abuse in College Students - Anggina, Dientyah Nur; Pratiwi, Ratih; Azzahra, Luqyana; Fortuna, Dewi (Yayasan Rumah Ilmu Professor, 2025)
Sexual violence, bullying, and drug abuse are social problems frequently experienced by students in higher education. The risk factors for these three problems are diverse, involving interacting psychosocial, environmental, and personal aspects. This article aims to provide a comprehensive review of the factors contributing to the increased risk of sexual violence, bullying, and drug abuse among college students. Using a literature review approach, this study compiled and analyzed relevant previous research findings from psychological, sociological, and public health perspectives. The findings indicate that factors such as academic pressure, domestic violence, mental health disorders, and the dynamics of social relationships on campus are key triggers. Furthermore, existing social norms in the campus environment, such as patriarchal culture and a lack of awareness of the importance of mental health, contribute to these conditions. This study also identifies the importance of preventative measures through sex education, student empowerment, and support from mental health and social services on campus. In conclusion, the risk factors for sexual violence, bullying, and drug abuse among college students are multidimensional, requiring a holistic, community-based approach to addressing them.